Anthropometric Study of the Humeral Torsion Angle and Its Sex- and Side-Related Variations: (Birat Journal of Health Sciences, 2025)
Introduction: The humerus plays a critical role in the evolution of the human upper limb, characterized by a torsional twist between its head and shaft, known as the Angle of Humeral Torsion (AHT). This angle is influenced by biological activity and functional use of the limb, with variations noted across populations and activity levels.Objectives: The present study offers a descriptive analysis of the humeral torsion angle in young adult individuals, with the goal of evaluating its variations among male and female.Methodology: The present cross-sectional study aimed to quantify and compare the AHT in a sample of young healthy adults and assess differences between sexes and sides. A total of 104 medical students (62 males, 42 females) aged 18–24 years from Nobel Medical College and Teaching Hospital, Nepal, were evaluated using a validated manual palpation technique.Results: Results showed a significantly higher (p < 0.001) mean AHT in males (35. 44± 1.78, N=124, rt and lt) compared to females (32.61 ± 1.25, N=84, rt and lt), with significant gender difference. Comparing right (34.64±2.20) and left (33.95±1.97) angle of torsion showed significant difference (p=0.017) reported bilaterally asymmetrical humeral torsion.Conclusions: Estimation of angle of humeral torsion (AHT) in healthy young adult male reported higher angle compared to females and higher angle in right side reporting significant difference. It indicated having larger angle of torsion in male and bilaterally asymmetry in AHT within individuals. The findings provide important anthropometric data relevant to Orthopedic and rehabilitative practices in the Nepalese population.